2022
DOI: 10.1177/20503121221113091
|View full text |Cite
|
Sign up to set email alerts
|

Complications of instrumental vaginal deliveries and associated factors in hospitals of Western Oromia, Ethiopia

Abstract: Objective: In developing countries like Ethiopia, there is lack of evidence that shows the magnitude and factors affecting complications of instrumental delivery. Most of the research done in Ethiopia was secondary data and lacks variables like socio-demographic factors, availability of cardiotocograph, number of traction, and who conducted delivery (qualification of health workers). So, this study tried to fill the gaps by conducting primary research with secondary data and adding those variables stated above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In our study maximum participants were of age group 20-24 years (41.6%) which is similar to study done by Shimalis et al 4 In their study mean age was 24.94 years and in Hubena Z7 mean age was 24.7 years. Our mean age was 24.93 ± 0.99.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study maximum participants were of age group 20-24 years (41.6%) which is similar to study done by Shimalis et al 4 In their study mean age was 24.94 years and in Hubena Z7 mean age was 24.7 years. Our mean age was 24.93 ± 0.99.…”
Section: Discussionsupporting
confidence: 90%
“…Fetal indication is fetal distress, after coming head in breech presentation. 4 Being a tertiary care centre of this region, complicated cases are referred to our hospital. Many of these need cesarean section or instrumental delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Ethiopia indicated that mothers who delivered via C-section had a 66% lower risk of newborn mortality compared to those who underwent SVD, primarily due to prolonged labor and other complications associated with SVD [27]. These findings were substantiated by studies conducted in Western Oromia, Ethiopia [75], Canada [76], and Southern Ethiopia [27].…”
Section: Discussionmentioning
confidence: 92%
“…This study found that neonates born to mothers who underwent instrumental deliveries were at a higher risk of neonatal mortality in comparison to those born via spontaneous vaginal delivery (SVD). A study in Ethiopia discovered that 45.7% of neonates delivered through instrumental methods experienced complications and had low APGAR scores, which are known risk factors for neonatal mortality [ 75 ]. The use of instruments during delivery, such as forceps or vacuum extraction, was associated with an increased risk of neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A neonate who is assisted by vacuum deliveries had a greater proportion of NICU admissions compared to spontaneous deliveries and the mortality rate was higher in the vacuum. 6 The obstetrician prefer vacuum than forceps due to its apparent increased safety and easy to use. Studies done in Europe and USA indicate showed similar commonest indication for vacuum delivery as our study, which includes prolonged second stage of labour, fetal distress, followed by prolonged second stage and poor maternal effort.…”
Section: Introductionmentioning
confidence: 99%